Handbook for process safety in laboratories and pilot plants : a risk-based approach (CCPS handbook, 2023)
"Fatal accidents in chemical laboratories and pilot plants are infrequent events but they do occur and can be prevented. Non-fatal accidents that are much more common can also be prevented so as to avoid significant physical harm to individuals as well as major damage to property and business interruption. This book provides guidance on "what" can be done from a management systems perspective to identify hazards and manage risks of "loss of containment" events in chemical laboratories and pilot plants. It provides examples of "how to" implement such practices and descriptions of a range of typically encountered process safety hazards typical controls based on current best practices."--